KEKUASAAN JAWA DALAM STRUKTUR KERAJAAN ISLAM AN PEWAYANGAN : SEBUAH ANALISIS STRUKTURALISME LEVI-STRAUS - Ansari, Isa (Institut Seni Indoensia Surakarta, 2010)
The purpose of this research is to ï¬nd a model of Javanese power structure by using the perspective ofÂ structuralism, Levi-Strauss. Material object of this research is the history of the pap-Islamic kingdom inÂ Java Starting fmm Demak, Pajang and Mataram Kingdoms, this is certainly an the contrary of theassumption of theoretical structuralism which makes history only supplement and not part of the dataÂ analyzed. The model structure is then transformed into lakon Wahyu Makhutarama. The source data usedÂ in this study consists of two types of data that is written data obtained fmm the writings that have beenrecorded, and research reports. Both data sources are the result of an interview recorded with a tapeÂ recorder. The results of this study indicate that the model is dialectical Javanese power structure consistingÂ of elements of thesis, antithesis. and synthesis. The model is transfarmative to puppet stories in particularÂ lakon wahyu Makhutarama in the Java power system, shows the dialectics of power in establishment ofÂ genealogical and transcendental.Keywords: Javanese Power, Structural Levi-Strauss, Dialectics